Carbon nanotubes@Ni3V2O8@NiCo2S4 nanosheets on Ni foam as a cathode for high-performance aqueous supercapacitors. (15th December 2021) - Chen, Yue; Long, Xiao; Zou, Situo; Yang, Mingzhe; Du, Yihe; Song, Xiaoqiang; Fu, Yujun; Li, Junshuai; Li, Yali; He, Deyan
Highlights: A composite electrode of CNTs@NVO@NCS was facilely prepared by the hydrothermal growth and subsequent electrodeposition. A high capacitance of 8722.0 mF cm−2 at 1 mA cm−2 is obtained. An energy density of up to 0.414 mWh cm−2 is delivered by the aqueous asymmetric supercapacitor. Abstract: Herein, a high-performance supercapacitor cathode composed of carbon nanotubes (CNTs)@Ni3 V2 O8 @NiCo2 S4 nanosheets (CNTs@NVO@NCS) on Ni foam (NF) is reported, in which the composite nanoparticles of CNTs and Ni3 V2 O8 (CNTs@NVO) and the NiCo2 S4 (NCS) nanosheets around CNTs@NVO are synthesized by hydrothermal growth and electrodeposition, respectively. A high specific capacitance of 8722.0 mF cm –2 at 1 mA cm –2 together with good rate performance, i.e., 7337.6 mF cm −2 at 16 mA cm −2 and 4560.0 mF cm −2 even at 60 mA cm −2 is delivered by the electrode. Cycling test indicates that ∼ 81.8% of its initial capacitance and ∼ 100% Coulombic efficiency over 10, 000 cycles at 10 mA cm −2 can be maintained. An aqueous asymmetric supercapacitor assembled using CNTs@NVO@NCS on NF as the cathode, the activated carbon on carbon cloth as the anode and the 2 M KOH aqueous electrolyte delivers good cycle performance with ∼ 14.1% total capacitance decay after 10, 000 cycles at 20 mA cm –2 and an energy density as high as 0.414 mWh cm –2 at 0.800 mW cm –2 . In view of facile preparation and excellent performance, this research provides a meaningful and valuable exploration for designing and fabricating high-performance cathodes and the related energy storage devices. Graphical abstract: Image, graphical abstract A high specific capacitance of 8722.0 mF cm –2 at 1 mA cm –2 and good rate performance are delivered.